Tumours of the Skull Base and Paranasal Sinuses - Gil, Ziv; Fliss, Dan M. (Head and Neck Cancer Clinics, 2012)
Recent developments in our understanding of the complex anatomy of the cranial base and the biological behaviour of tumours in this area have significantly improved the outcome of patients with skull base tumours. The contributors present a systemic introduction and summary of contemporary knowledge in skull base surgery. The book has three major parts: (i) clinical, pathological and radiological management of patients, (ii) open and endoscopic surgical approaches to the skull base, and (iii) outcome, morbidity and postoperative follow-up of patients. The book is meant for medical students, residents and consultants in various disciplines, including otolaryngology, head and neck surgery, neurosurgery, plastic surgery, maxillofacial surgery and oncology. The emphasis is on the clinical approach to the patient rather than on surgical techniques per se.  .